Vanmanenia intermedia Fang, 1935, a valid hill-stream species of loach (Teleostei: Gastromyzontidae) from the middle Yangtze River basin, Southwest China - Deng, Shu-Qing; Zhang, E (Zootaxa, 2020)
Vanmanenia intermedia, which has long been synonymized with V. pingchowensis since 1980, is here revalidated using morphological characters and molecular evidences, and redescribed on the basis of topotypic specimens. This species is distinguished from all other congeneric species by the following combination of characters: triangular-shaped rostral lobules without secondary rostral barbels; distal edge of dorsal-fin slightly concave; no longitudinal black stripe on the flank; a longer snout (length 52.6–64.5 % of HL); a more backwards-placed anus (the vent to anal distance 34.7–46.1% of the pelvic to anal distance); a slender caudal peduncle (depth 9.1–11.3 % of SL); a longer anal-fin base (length 7.5–9.5 % of SL); and a smaller gill opening with its upper extremity closer to the level of the lower margin of the orbit. The validity of V. intermedia is also confirmed by its significant cyt b gene sequence divergence with all sampled congeneric species and its monophyly recovered in the cyt b gene-based phylogenetic analysis.